Role Bhabinkamtibmas through Binmas Online System v2 to Prevent Motor Vehicle Theft in the Jurisdiction of Magetan Police - Ekber Bauromi; Muhammad Imam Farid (Tanggon Kosala, 2024)
This study is done with the background of the existing criminal motor vehicle theft case in Magetan Regency. Motor Vehicle Theft cases have become common and still occur in Magetan. To create a conducive Kamtibmas situation, Bhabinkamtibmas must approach the community. This study aims to explain the role of Bhabinkamtibmas with the Binmas Online System V2 (BOSV2) to prevent motor vehicle theft in the jurisdiction of the Magetan Police and to determine the factors that influence the use of Binmas Online System V2 (BOSV2) by Bhabinkamtibmas of the Magetan Police to prevent motor vehicle theft. The theory used for analysis is the 6M theory and the SWOT analysis theory. The concepts used as the theoretical basis are the Bhabinkamtibmas concept, the BOSV2 concept, and the Curanmor concept. The approach used in this study is qualitative, with a tendency to explain descriptive analysis. Information obtained in this research process is obtained through primary and secondary data sources. Then, the data collection techniques were used: observation, interview, and study documents. Based on the results of the research, the role Bhabinkamtibmas use in preventing theft of motorized vehicles through the Binmas Online System V2 is not optimal, as indicated by the lack of understanding of how to operate the BOSV2 application. Therefore, this study provides suggestions for implementation improvement, learning, and mastery of function Binmas technical, especially Bhabinkamtibmas through the polribelajar.id program and ratified regulations regarding the operation of BOSV2 so that there is a definite reference in its use.